The effect of nebivolol and ramipril on selected biochemical parameters, arterial stiffness, and circadian profile of blood pressure in young men with primary hypertension: A 12-week prospective randomized, open-label study trial. Issue 30 (July 2018) - Walczak-Gałęzewska, Marta; Szulińska, Monika; Miller-Kasprzak, Ewa; Pupek-Musialik, Danuta; Bogdański, Paweł
Abstract: Background: The pleiotropic effects of hypotensive drugs should always be taken into consideration. There is limited data on the effect of such drugs on reducing global cardiovascular risk in young hypertensives. The aim of this study was to evaluate the effect of nebivolol and ramipril on biochemical parameters, arterial stiffness, and circadian profile of blood pressure (BP) in young men undergoing treatment for hypertension (HT). Methods: A total of 80 patients aged 16 to 28 years of age with grade 1 HT were enrolled into the prospective randomized, open-label trial. They were randomized to receive 5 mg of nebivolol or 5 mg of ramipril, daily. Arterial stiffness index (SI), the circadian profile of BP registered in ambulatory blood pressure monitoring (ABPM), and biochemical parameters—including lipid profile, insulinemia, glycemia, and high sensitivity C-reactive protein (hsCRP) levels—were evaluated before and after the twelve-week period. Results: After the treatment period, we observed significant decreases in both ABPM systolic blood pressure (SBP) in group of nebivolol ( P  = .0007) and ramipril ( P  = .0001) and in ABPM diastolic blood pressure (DBP) in group of nebivolol ( P  = .0018) and ramipril ( P  = .0006). Reductions in the nondippers percentage were found in group of nebivolol and ramipril ( P  = .0077, P  = .0001 respectively). Ramipril treatment resulted in a significant plausible modification in high-density lipoprotein (HDL) ( P  = .0390), glucose ( P  = .0213), and hsCRP ( P  = .0053) concentrations, as well as decreased SI ( P  = .0009) value, while nebivolol treatment showed no such benefits. Conclusions: Despite the similar hypotensive effect of nebivolol and ramipril, ramipril seems to possess better clinical potential in reducing cardiovascular risk in young men with HT.